Optimal targeting in fundraising: A machine-learning approach - Tobias Cagala; Ulrich Glogowsky; Johannes Rincke; Anthony Strittmatter (Johannes Kepler University of Linz, Department of Economics, 2021)
Ineffective fundraising lowers the resources charities can use for goods provision. We combine a field experiment and a causal machine-learning approach to increase a charity's fundraising effectiveness. The approach optimally targets fundraising to individuals whose expected donations exceed solicitation costs. Among past donors, optimal targeting substantially increases donations (net of fundraising costs) relative to benchmarks that target everybody or no one. Instead, individuals who were previously asked but never donated should not be targeted. Further, the charity requires only publicly available geospatial information to realize the gains from targeting. We conclude that charities not engaging in optimal targeting waste resources.
Keywords: C93; D64; H41; L31; C21; 330; Fundraising; charitable giving; gift exchange; targeting; optimal policy learning; individualized treatment rules